Targeted delivery of 5-fluorouracil to HT-29 cells using high efficient folic acid-conjugated nanoparticles. (February 2015) - Wang, Yichao; Li, Puwang; Chen, Lijue; Gao, Weimin; Zeng, Fanbo; Kong, Ling Xue
Abstract The incorporation of a high percentage of targeting molecules into drug delivery system is one of the important methods for improving efficacy of targeting therapeutic drugs to cancer cells. PLGA-based drug delivery carriers with folic acid (FA) as targeting molecule have a low targeting efficiency due to a low FA conjugation ratio. In this work, we fabricated a FA-conjugated PLGA system using a crosslinker 1, 3-diaminopropane and have achieved a high conjugation ratio of 46.7% (mol/mol). The as-prepared PLGA-based biomaterial was used to encapsulate therapeutic drug 5-fluorouracil (5-FU) into nanoparticles. In the in vitro experiments, an IC50 of 5.69 µg/mL has been achieved for 5-FU loaded PLGA-1, 3-diaminopropane-folic acid nanoparticles on HT-29 cancer cells and is significantly lower than that of 5-FU and 5-FU loaded PLGA nanoparticles which only have an IC50 of 22.9 and 14.17 µg/mL, respectively. The fluorescent microscopy images showed that nanoparticles with FA are largely taken up by HT-29 cancer cells and the targeting nanoparticles have more affinity to cancer cells than the pure drugs and untreated nanoparticles. Therefore, the 1, 3-diaminopropane can facilitate the conjugation of FA to PLGA to form a novel polymer and 5-FU loaded PLGA-1, 3-diaminopropane-folic acid nanoparticles can be a highly efficient system for specific delivery of drugs to cancer cells.